Risk factors for anastomotic leakage and its impact on long-term survival in left-sided colorectal cancer surgery - Marius Kryzauskas; Augustinas Bausys; Austeja Elzbieta Degutyte; Vilius Abeciunas; Eligijus Poskus; Rimantas Bausys; Audrius Dulskas; Kestutis Strupas; Tomas Poskus (World Journal of Surgical Oncology, 2020)
Abstract Background Anastomotic leakage (AL) significantly impairs short-term outcomes. The impact on the long-term outcomes remains unclear. This study aimed to identify the risk factors for AL and the impact on long-term survival in patients with left-sided colorectal cancer. Methods Nine-hundred patients with left-sided colorectal carcinoma who underwent sigmoid or rectal resection were enrolled in the study. Risk factors for AL after sigmoid or rectal resection were identified, and long-term outcomes of patients with and without AL were compared. Results AL rates following sigmoid and rectal resection were 5.1% and 10.7%, respectively. Higher ASA score (III–IV; OR = 10.54, p = 0.007) was associated with AL in patients undergoing sigmoid surgery on multivariable analysis. Male sex (OR = 2.40, p = 0.004), CCI score > 5 (OR = 1.72, p = 0.025), and T3/T4 stage tumors (OR = 2.25, p = 0.017) were risk factors for AL after rectal resection on multivariable analysis. AL impaired disease-free and overall survival in patients undergoing sigmoid (p = 0.009 and p = 0.001) and rectal (p = 0.003 and p = 0.014) surgery. Conclusion ASA score of III–IV is an independent risk factor for AL after sigmoid surgery, and male sex, higher CCI score, and advanced T stage are risk factors for AL after rectal surgery. AL impairs the long-term survival in patients undergoing left-sided colorectal surgery.